2023
DOI: 10.3390/su15043672
|View full text |Cite
|
Sign up to set email alerts
|

Locality in the Promoted Sustainability Practices of Michelin-Starred Restaurants

Abstract: Sustainable practices are increasingly promoted in the restaurant industry. One significant aspect of sustainability in restaurants is the use of local supply chains, especially for food, which also serve as a means for restaurants to promote freshness of produce, sourcing, and quality. Considering the prevalence of locality in menu marketing, this study aims to explore the relationships between sustainability and locality at fine-dining restaurants. Michelin-starred restaurants are significant influencers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 102 publications
0
0
0
Order By: Relevance
“…Previous studies have found that destination restaurants could demonstrate locality in various ways during the processes of procurement, preparation, presentation, and promotion [ 7 , 34 ]. This study further introduces four main practices related to promote locality: sourcing local foods during procurement [ 44 , 45 , 46 ], introducing local culinary culture in the menu during preparation [ 40 , 47 , 48 ], demonstrating the restaurant servicescape with locality elements during presentation [ 49 , 50 , 51 ], and establishing restaurant reputation during promotion [ 52 , 53 , 54 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have found that destination restaurants could demonstrate locality in various ways during the processes of procurement, preparation, presentation, and promotion [ 7 , 34 ]. This study further introduces four main practices related to promote locality: sourcing local foods during procurement [ 44 , 45 , 46 ], introducing local culinary culture in the menu during preparation [ 40 , 47 , 48 ], demonstrating the restaurant servicescape with locality elements during presentation [ 49 , 50 , 51 ], and establishing restaurant reputation during promotion [ 52 , 53 , 54 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Proximity is the key to understanding local foods, including geographical proximity; relational proximity; and social, economic, and environmental proximity [34]. Scholars reviewed two decades of research on local food systems and generalised eight benefits of LFS within the perspectives of consumers, farmers, community, and environment [57]: (1) increasing consumers' access to fresh and healthy food; (2) strengthening consumer willingness to pay more for local over non-local foods; (3) enhancing farmers' sense of social recognition; (4) economically benefiting farmers; (5) increasing local community ties; (6) benefiting the local economy; (7) fostering environmentally friendly production practices; and (8) helping mitigate climate change. Nevertheless, a number of perceived barriers to restaurant procurement of local foods have been identified, including a lack of knowledge, inconvenient ordering and delivery times, limited availability of products, variable costs, packaging and handling, and inadequate distribution systems [58,59].…”
Section: Restaurant Practices That Introduce Localitymentioning
confidence: 99%
See 3 more Smart Citations